2018
DOI: 10.1155/2018/3562701
|View full text |Cite
|
Sign up to set email alerts
|

The Analgesic Efficacy of Transverse Abdominis Plane Block versus Epidural Block after Caesarean Delivery: Which One Is Effective? TAP Block? Epidural Block?

Abstract: Introduction and Objective TAP block has gained popularity to provide postoperative analgesia after abdominal surgery but its advantage over epidural analgesia is disputed. For lower abdominal surgeries, epidural analgesia has been the gold standard and time-tested technique for providing postoperative analgesia, but contraindications for the same would warrant need for other equally good analgesic techniques. The objective of this study is to compare the analgesic efficacy of both the techniques. Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 15 publications
0
18
0
4
Order By: Relevance
“…Of the initial 3213 unique article citations identified by the search strategy, 18 randomised controlled trials fulfilled the inclusion criteria [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Details of the screening process are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the initial 3213 unique article citations identified by the search strategy, 18 randomised controlled trials fulfilled the inclusion criteria [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Details of the screening process are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 placed [19,26]. In nine trials, the approach of the TAP block was lateral [15,16,18,19,24,[26][27][28][29], whereas it was subcostal in four trials [21][22][23]30] and combined or either lateral or subcostal in five trials [14,17,20,25,31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 TAP block has gained popularity as an effective analgesia technique in mothers undergoing cesarean delivery and works by blocking the anterior rami of the spinal nerves of the abdominal anterior wall after spreading of the local anaesthetic agent in the neurofascial plane between the internal oblique and transversus abdominis muscle, thereby relieving the pain of cesarean section. 5 Recent publications have demonstrated that the ESP block serves as a practical component of a multimodal regimen for pain relief after various types of operations, including cesarean delivery, by blocking both the dorsal and ventral branches of the thoracic and abdominal spinal nerves; therefore, it provides both somatic and visceral analgesia. 4,6 We hypothesized that bilateral ESP block would provide more effective and prolonged pain relief than TAP block after elective cesarean delivery and could be used as part of a multimodal opioid-sparing analgesia technique.…”
Section: Introductionmentioning
confidence: 99%
“…Pregledni članci i metaanalize sugeriraju da bi blok TAPa nakon tradi cionalnog SCa mogao biti posebno učinkovit pri smanjenju poslijeoperacijske boli i manjoj konzuma ciji opioida, a ujedno i komplikacija vezanih uz opioi de. [9][10][11] Prema dosad objavljenoj literaturi, sugerira se da bi blok TAPa trebalo primjenjivati kod SCa koji su rađeni u općoj anesteziji i u rodilja kojima nisu davani dugodjelujući neuroaksijalni opioidi 9,[12][13][14] Trenutačno ne postoje specifične smjernice za anesteziju ekstrape ritonealnih SCa i, prema našim saznanjima iz litera ture, ne nalazimo istraživanja o učinkovitosti bloka TAPa kod FAUCSa ili drugih vrsta ekstraperitoneal nih SCa. Zbog toga ne možemo usporediti svoja isku stva s iskustvima drugih.…”
Section: Raspravaunclassified